Perspektif kebudayaan Sunda dalam kesatuan bangsa Indonesia : dan esai-esai lainnya mengenai kebudayaan Sunda. (Bandung : Pusat Studi Sunda, 2011)
Social life and customs of Sundanese people; collection of articles.
Mengandungi rujukan bibliografi.
Indonesian, English, and Sundanese.
Keywords: Sundanese (Indonesian people).; Indonesia -- Social life and customs